Flow fouling and static scaling characterisation of micro/nanostructure enchanced metal alloys - Wong, Gabriel Heng Yew (Nanyang Technological University, 2023)
This final-year project aims to investigate fouling and scaling characteristics on metal alloy surfaces and develop effective anti-fouling/scaling strategies. The research involves utilizing existing methods and techniques to prevent scaling by applying superhydrophobic (SHP) coatings and slippery liquid-infused porous surfaces (SLIPSs) on metal alloy substrates.